A systematic review of liposomal nanofibrous scaffolds as a drug delivery system: a decade of progress in controlled release and therapeutic efficacy - Houssam Aaref Abboud; Romána Zelkó; Adrienn Kazsoki (Drug Delivery)
Drug-loaded liposomes incorporated in nanofibrous scaffolds is a promising approach as a multi-unit nanoscale system, which combines the merits of both liposomes and nanofibers (NFs), eliminating the drawback of liposomes’ poor stability on the one hand and offering a higher potential of controlled drug release and enhanced therapeutic efficacy on the other hand. The current systematic review, which underwent a rigorous search process in PubMed, Web of Science, Scopus, Embase, and Central (Cochrane) employing (Liposome AND nanofib* AND electrosp*) as search keywords, aims to present the recent studies on using this synergic system for different therapeutic applications. The search was restricted to original, peer-reviewed studies published in English between 2014 and 2024. Of the 309 identified records, only 29 studies met the inclusion criteria. According to the literature, three different methods were identified to fabricate those nanofibrous liposomal scaffolds. The results consistently demonstrated the superiority of this dual system for numerous therapeutic applications in improving the therapy efficacy, enhancing both liposomes and drug stability, and releasing the encapsulated drug in a proper sustained release without significant initial burst release. Merging drug-loaded liposomes with NFs as liposomal nanofibrous scaffolds are a safe and efficient approach to deliver drug molecules and other substances for various pharmaceutical applications, particularly for wound dressing, tissue engineering, cancer therapy, and drug administration via the buccal and sublingual routes. However, further research is warranted to explore the potential of this system in other therapeutic applications.